IMPLEMENTASI PERATURAN DAERAH KABUPATEN CIREBON NOMOR 7 TAHUN 2014 TENTANG PENATAAN, PEMBINAAN PASAR TRADISIONAL, PUSAT PERBELANJAAN DAN TOKO MODERN - Rinaldi, Rio; Hidayat, Zainal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Implementation of Regional Regulation Number 7 of 2014 About Planning, Development of Traditional Markets, Shopping Centers and Modern Stores departing from problem structuring and development of traditional markets, shopping centers and modern stores are paying less attention and protect the human rights community in the trade sector. The purpose of this study was to describe how the implementation of local regulations number 7 of 2014 regarding the arrangement, development of traditional markets, shopping centers and modern shops can be assessed through the fulfillment of its principles. In this study the researchers intend to analyze the factors that hinder the implementation of local regulations number 7 of 2014 regarding the arrangement, development of traditional markets, shopping malls and modern shops. This research uses descriptive research by observation in the field. The results of this study are still encountering many obstacles on several fulfillment principle. Among these factors, the allocation of financial resources, keterpautan and support among various implementing agencies, clarity and consistency of the rules, forces commitment to the policy objectives and broad access outside groups to participate in the implementation of the policy. The study recommends among other things, the need to support financial resources, increased keterpautan and support among various implementing agencies, the need for clarity and consistency of the rules, increased commitment of forces, and increased access to outside groups.